Unseen universe : new secrets of the cosmos revealed by the James Webb Space Telescope - Harper, Caroline (Greenfinch, an imprint of Quercus Editions Ltd, 2024)
"This is the universe as you've never seen it before. Discover how the awe-inspiring images from Webb are rapidly changing our understanding of our solar system and beyond."--Amazon.